Energy System Audit Measurement at R.S. Bhayangkara H. S. Samsoeri Mertojoso Surabaya - Agus Kiswanto; Edo Rahardian Arfelindo (JEECS (Journal of Electrical Engineering and Computer Sciences), 2022)
Bhayangkara H.S. Samsoeri Mertojoso Surabaya Hospital is a public service agency (BLU) engaged in public health services and a member of the governmental police. The hospital certainly has electricity. This power source must be controlled honestly and as much as possible. This is used to get stable and maximum electrical energy. For this reason, weekly checks and measurements are required. In addition to inspection, of course it is necessary to clean every nook and cranny of electrical equipment such as wires. According to the researchers' observations, this time the power supply occurred at this hospital was noisy or unstable. This is proven to be because the filler material used is still suboptimal, which causes discomfort for the nurse and, of course, the patient. With this in mind, of course, we need a voltage and current that maintains maximum power.